2012
DOI: 10.1111/j.1440-172x.2011.01981.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of perceived barriers of pain management in Iranian children: A qualitative study

Abstract: Hospitalized children are often inadequately treated for their pain. Paediatric nurses experience these inadequacies more than other health-care team members. This research was an attempt in the form of a phenomenological study to reveal some major barriers in children pain management as the nurses had perceived. Sixteen nurses were interviewed in the medical, surgical and infectious paediatric wards of a hospital in Iran. Data analysis were based on Colaizzi method that surfaced three main themes in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…; Namnabati et al. ), children's behaviour was reported as a barrier to effective identification and management of pain. In Sweden, 20 nurses were interviewed about the factors influencing their abilities to assess and manage children's pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Namnabati et al. ), children's behaviour was reported as a barrier to effective identification and management of pain. In Sweden, 20 nurses were interviewed about the factors influencing their abilities to assess and manage children's pain.…”
Section: Resultsmentioning
confidence: 99%
“…In another qualitative study of 16 nurses in Iran, nurses said that assessment of pain in young children was problematic due to their limited verbal expressions and behavioural responses to pain (Namnabati et al. ). These findings concur with those of other studies (McInerney et al.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of pain in a child may be influenced by the parent (118,(125)(126)(127) and the physical and social context (128) in which the assessment takes place. Studies have shown that ward culture impacts pain assessment practices (126,129) and nurses often attribute deficiencies in pain assessment practices to staffing issues and heavy workloads (15,(130)(131)(132).…”
Section: Factors Influencing the Assessment And Management Of Painmentioning
confidence: 99%
“…[19][20][21][22][23] Overall, related literature was generated as a result of theoretical debate rather than empirical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of this, to date, the available studies are largely descriptive, driven by quantitative data, inclusive only of senior nurses, and focused exclusively on chronic pain, cancer and critically ill patients. [19][20][21][22][23] Overall, related literature was generated as a result of theoretical debate rather than empirical investigations.…”
Section: Introductionmentioning
confidence: 99%